The correlation of muscle morphology with variations of 10-repetition maximum bench press strength in resistance-trained subjects - Josef Fischer; Christian Burger; Josefina Manieu Seguel; Adrian Schöpflin; Coşkun Rodoplu; Andreas Konrad (Bern Open Publishing, 2024)
The relationship between muscle mass and strength is complex as it can be influenced by several neurological factors. Variations in the type of training and its mechanisms involved, such as strength- or hypertrophy-oriented training, may influence this relationship in different ways (Carvalho et al., 2022). In addition, the relationship between muscle stiffness and strength remains unclear (Akagi et al., 2016; Mannarino et al., 2019). Thus, this research aimed to investigate the potential correlation between the strength levels, measured by the 10-repetition maximum (10RM), across different ranges of motion (ROM) in the barbell bench press exercise (BP) to the cross-sectional area (CSA) and shear modulus (= indication for stiffness) of the muscles primarily engaged in the exercise. Twenty-one resistance-trained participants (age 27.1 ± 3.4 years) volunteered in this study. The CSA and muscle shear modulus were assessed in a resting position with ultrasound imaging using an ultrasound system (Supersonic Imaging, Aix-en-Provence, France). CSA ultrasound images were captured with panoramic mode for the pectoralis major and the triceps brachii long head. Muscle shear modulus was measured for the pectoralis major, the anterior deltoid, and the triceps brachii long head using shear wave elastography (SWE). Additionally, participants were assessed for their 10RMs of the three types of BP variations, a full ROM and two partial ROMs, the upper half and lower half of the full movement. Data analyses revealed significant correlations between all BP variations and the medial and lateral CSA of the pectoralis major with correlations ranging from r = 0.775 to r = 0.832 (p = 0.001). Significant correlations were also found for the proximal CSA of the triceps brachii long head with the strength values of all tested BP variations with correlations ranging from ρ = 0.492 to ρ = 0.494 (p = 0.028 to p = 0.027). The distal CSA of the triceps brachii did only correlate significantly with the lower ROM BP (r = 0.484, p = 0.026). No significant correlations were found between the SWE of the measured muscles and the bench press variations tested. Additionally, no differences were observed in the correlations between the BP variations. Correlations between 10RM strength levels and the CSA of the pectoralis, and to a lesser extent, the triceps muscle, show the significance of muscle mass for strength in resistance-trained individuals. This finding aligns with a previous training study that examined the hypertrophic effects of bench press exercises on various muscles (Ogasawara et al., 2012). The study revealed that although both the pectoralis and triceps muscles increased in size, the triceps tended to plateau earlier. This suggests that the pectoralis muscle has a greater capacity for muscle volume growth and, consequently, a higher potential for force production. Finally, SWE measurements revealed no significant correlation with BP variations, implying that muscle stiffness may not play as critical a role in 10RM performance as muscle CSA does. This conclusion aligns with other studies that could not find significant changes in muscle stiffness using SWE following resistance training interventions (Dankel & Razzano, 2020). References Akagi, R., Shikiba, T., Tanaka, J., & Takahashi, H. (2016). A six-week resistance training program does not change shear modulus of the triceps brachii. Journal of Applied Biomechanics, 32(4), 373-378. https://doi.org/10.1123/jab.2015-0290 Carvalho, L., Junior, R. M., Barreira, J., Schoenfeld, B. J., Orazem, J., & Barroso, R. (2022). Muscle hypertrophy and strength gains after resistance training with different volume-matched loads: A systematic review and meta-analysis. Applied Physiology, Nutrition, and Metabolism, 47(4), 357-368. https://doi.org/10.1139/apnm-2021-0515 Dankel, S. J., & Razzano, B. M. (2020). The impact of acute and chronic resistance exercise on muscle stiffness: A systematic review and meta-analysis. Journal of Ultrasound, 23(4), 473-480. https://doi.org/10.1007/s40477-020-00486-3 Mannarino, P., Matta, T. T. D., & Oliveira, L. F. D. (2019). An 8-week resistance training protocol is effective in adapting quadriceps but not patellar tendon shear modulus measured by Shear Wave Elastography. PLoS ONE, 14(4), Article e0205782. https://doi.org/10.1371/journal.pone.0205782 Ogasawara, R., Thiebaud, R. S., Loenneke, J. P., Loftin, M., & Abe, T. (2012). Time course for arm and chest muscle thickness changes following bench press training. Interventional Medicine and Applied Science, 4(4), 217-220. https://doi.org/10.1556/imas.4.2012.4.7